Question of the Interpretation of Presidential Inauguration Institute by the Constitution of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article deals with the Question of the Interpretation of Presidential Inauguration Institute by the Constitution of the Republic of Kazakhstan. Most often they are expressed, or that it is not clear how to apply the constitutional provision, or appear two or more variants of its application, but mutually to each other exclusive. And then you want the official interpretation of the Constitution. The author analyzes the article 42 of the Constitution of the Republic of Kazakhstan.Key words: President’s inauguration, the Constitution, the rule of law, law reform.